The frequency and nature of prescribing problems by GPs- in- training (REVISiT): a retrospective review. Issue 3 (2022) - Salema, Nde-Eshimuni; Bell, Brian G; Marsden, Kate; Gookey, Gill; Swanwick, Glen; Bassi, Mindy; Mehta, Rajnikant
No abstract available